2016
DOI: 10.1590/2359-3997000000135
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in infertile women with polycystic ovarian syndrome

Abstract: Objective: The aim of the present study was to determine the prevalence of metabolic syndrome (MS) in infertile Iranian women with polycystic ovary syndrome (PCOS) using the ATPIII criteria. Subjects and methods: In this cross-sectional study, 624 women with PCOS were enrolled at a tertiary referral center in Tehran, Iran, between April, 2012 and March, 2013. Diagnosis of MS was according to ATPIII criteria. Also, we divided PCOS patients into following two main groups: (i) with MS (n = 123) and (ii) without M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Acanthosis nigricans, observed in 48.19% of the patients, cannot be forgotten, since a substantial percentage of PCOS patients suffer from this condition and its severity correlates with the degree of IR. 26 Besides that, the metabolic abnormalities in PCOS patients can coincide with the diagnostic components of the MS, 9 in which IR and compensatory hyperinsulinemia also play a crucial role in the physiopathology of the MS. 27 Nevertheless, the prevalence of this syndrome can vary depending on the ethnicity, age, BMI, country, as well as the criteria used in defining both PCOS and the MS. 28 Despite having excluded the analysis the patients' charts with fasting glucose higher than 100 mg/dL, 22.89% of the patients in our study had at least three parameters altered the normalcy standards, which would comply with the MS diagnostic criteria, 9 reinforcing the higher cardiovascular risk in PCOS women.…”
Section: Discussionmentioning
confidence: 78%
“…Acanthosis nigricans, observed in 48.19% of the patients, cannot be forgotten, since a substantial percentage of PCOS patients suffer from this condition and its severity correlates with the degree of IR. 26 Besides that, the metabolic abnormalities in PCOS patients can coincide with the diagnostic components of the MS, 9 in which IR and compensatory hyperinsulinemia also play a crucial role in the physiopathology of the MS. 27 Nevertheless, the prevalence of this syndrome can vary depending on the ethnicity, age, BMI, country, as well as the criteria used in defining both PCOS and the MS. 28 Despite having excluded the analysis the patients' charts with fasting glucose higher than 100 mg/dL, 22.89% of the patients in our study had at least three parameters altered the normalcy standards, which would comply with the MS diagnostic criteria, 9 reinforcing the higher cardiovascular risk in PCOS women.…”
Section: Discussionmentioning
confidence: 78%
“…Apparently, the incidence of MS among PCOS patients seems to be affected also by the geographical region as well as the habits of the patients as it has been recently shown that in Iran the incidence of MS in the Iranian PCOS patients (19.7%) is less than that seen in United States (33–46%) (8), India (9) and Brazil (10) and its incidence increases with age and body mass index (BMI), with the most prevalent condition being low/high density lipoprotein-cholesterol (11). On the other hand, the incidence of MS was reported to be lower among European women with PCOS (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…(28). Insulin resistance may result in chronic anovulation and infertility with hyperandrogenism (29). Metabolic syndrome is associated with hypogonadism in both men and women.…”
Section: Introductionmentioning
confidence: 99%